Implementasi Pengembangan Kompetensi Aparatur Sipil Negara Dalam Rangka Pemenuhan Hak Pegawai Negeri Sipil Di Provinsi Sumatera Barat - Khairani; Sri Artnetti; Fikri Hasan (Magister of Law, Faculty of Law, University of Mataram, 2023)
This study aims to know the implementation of competency development for Civil Servants (PNS) in West Sumatra. As an element of the state apparatus, civil servants have the right to participate in the development so that their competence in providing public services can possibly be carried out in a professional and qualified manner. The results of this study are expected to contribute to local government policies in managing the ASN. Based on Article 70 of Law Number 5 of 2014 concerning State Civil Apparatus (UU ASN) which states that every ASN employee has the right and opportunity to develop their competency, each Government Agency is required to prepare an annual competency development plan that is included in the annual work plan of the respective agency's budget. This can have an impact on the competence of less effective personnel, causing their responsibilities to be carried out inefficiently and negatively impacting the quality of public services. The issues in this study: 1. How is the management of civil servants in West Sumatra Province? 2. How is the competency development of civil servants in West Sumatra Province implemented? The research method used is a sociological juridical (empirical) approach. This research is descriptive and analytical. The data are collected through interviews and document studies. This research aligns with the strategic research plan set by Andalas University for 2020 – 2024, which is focused on the issue of political and social law. The results of the study show that the management of PNS in West Sumatra Province has not been based on a comparison of the competencies and qualifications required by positions with the competencies and qualifications held by the PNS, owing to the merit system’s ineffective implementation in PNS management. Implementation of PNS Competency Development in West Sumatra Province, from the data obtained, only 1,168 out of 18,614 civil servants in West Sumatra Province participated in PNS competency development, and the annual competency development plan document was not prepared, this shows that it is still not optimal and the implementation is not yet appropriate between civil servant competency development and applicable regulations.